Talent identification and the relative age effect in New Zealand rowing - Blackmore, M.; Slade, D. G. (New Zealand Physical Educator, 2019)
Post the 1970's New Zealand has enjoyed an increasingly high international profile in rowing. In the last two Olympics, Rowing New Zealand (RNZ) athletes have accumulated five (5) gold, one (1) silver and two (2) bronze medals - eight medals in total. Given our distance from our main competition in Europe and the expense of the sport this has been a significant achievement. Contributing to that performance in no small way is the talent identification (TID) and development of secondary school students by RNZ. This achievement is also noteworthy given that the relatively small pool of competitors in secondary school rowing1. Only 4000 secondary school students are registered as rowers, with more than half of that number classified as novices. This investigation sought to examine the talent identification processes of RNZ that appeared to be at the heart of this success. It sought to establish if RNZ was aware of the relative age effect (RAE) in TID and whether what they did in their programmes represented best practice.